IL-10-producing regulatory B cells are decreased in patients with psoriasis. Issue 2 (February 2016) - Hayashi, Mitsuha; Yanaba, Koichi; Umezawa, Yoshinori; Yoshihara, Yuki; Kikuchi, Sota; Ishiuji, Yozo; Saeki, Hidehisa; Nakagawa, Hidemi
Highlights: The frequency of B10 cells in psoriasis is decreased. The frequency of B10 progenitor cells in psoriasis is increased. Treatment with immunosuppressants corrects the abnormalities of B10 cells. Serum BAFF levels are decreased in patients with psoriasis. Treatment with immunosuppressants reduces the serum BAFF levels in psoriasis. Abstract: Backgrounds: Interleukin (IL)-10-producing regulatory B cells (B10 cells) have been shown to ameliorate psoriasis in mice. Human B10 progenitor cells are characterized as CD19 + CD24 hi CD38 hi B cells that exert their regulatory functions via the production of IL-10. However, the role of B10 cells in the pathogenesis of psoriasis remains unclear. Objectives: We examined B10 cells in patients with psoriasis and healthy controls. Methods: Peripheral blood mononuclear cells were isolated from psoriasis patients without a history of receiving any immunosuppressants during the 6-month period before enrollment in the study. Using flow cytometry, we determined the frequencies of blood B cell subsets, B10 progenitor cells, and B10 cells for 31 patients with psoriasis and 26 healthy controls. Results: Both psoriasis patients and healthy controls showed similar frequencies of total B cells, IgD + CD27 − naïve B cells, and IgD − CD27 + memory B cells. However, the frequency of CD19 + CD24 hi CD38 hi B10 progenitor cells was significantly higher in patients with psoriasis than in the healthy controls. In contrast, the frequency of B10 cells in patients with psoriasis was significantly lower than that in healthy controls. Furthermore, treatment with immunosuppressants resulted in a decrease in B10 progenitor cells and an increase in B10 cells. Conclusion: B10 progenitor cells were increased, while IL-10-producing regulatory B10 cells were decreased in patients with psoriasis, suggesting that B10 cells may be functionally impaired in patients with psoriasis.